Pemahaman Konsep IPAS melalui Penerapan Model Pembelajaran Role Playing pada Materi Rantai Makanan di Sekolah Dasar : A Systematic Literature Review - Ramadani, Nofeni; Al Fath, Ayatullah Muhammadin; Hutagalung, Erwin Efendi (Universitas Muhammadiyah Magelang, 2026)
This study aims to evaluate and synthesize previous research findings regarding the use of the role-playing learning model in enhancing science concept understanding among elementary school students, particularly on the topic of food chains. This study employed a Systematic Literature Review (SLR) method using the PRISMA 2020 protocol, which includes identification, screening, eligibility, and inclusion stages. The data analyzed consisted of 14 scientific articles obtained from databases such as Google Scholar, ERIC, ResearchGate, and Garuda, published between 2020 and 2026. The results indicate that the role-playing model consistently improves students’ understanding of science concepts through active, interactive, and contextual learning processes. In addition, this model contributes positively to students’ learning outcomes, motivation, and social skills, particularly in communication and collaboration. However, the effectiveness of this model is highly dependent on the quality of classroom implementation, student readiness, and the accuracy of lesson planning. Therefore, the role-playing model can be considered an effective instructional strategy in elementary science education, especially for explaining abstract concepts such as food chain processes.